2008
DOI: 10.2298/avb0806487k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different dietary crude protein levels on performance, N digestibility and some blood parameters in Kivircik lambs

Abstract: In this study, 45 weaned Kivircik male lambs with an average initial body weight ŠBW¹ of 26.23 kg were randomly assigned to five experimental groups (G10, G12, G14, G16, G18) fed 10, 12, 14, 16, 18 % crude protein (CP), respectively. It was observed that G16 had higher BW than the first three groups (p<0.05), but there were no significant differences between G16 and G18. G16 had higher daily body weight gain ŠBWG¹ than other groups. During the study, when compared with first three groups, G16 had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
4
6
0
Order By: Relevance
“…In this study, the feed intake of the three experimental groups ranged from 1.215 to 1.254 g/day. These results support those of Bilal et al [8] who reported that the lowest dry matter intake was observed at the 10% CP level. Also, many researchers have reported no effect of dietary CP content on DMI [23,24] .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, the feed intake of the three experimental groups ranged from 1.215 to 1.254 g/day. These results support those of Bilal et al [8] who reported that the lowest dry matter intake was observed at the 10% CP level. Also, many researchers have reported no effect of dietary CP content on DMI [23,24] .…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the average final weight was highest (P<0.05) for the 17% CP diet, followed by 14 and 11% (Table 2). Improved growth performance was also reported at higher dietary CP levels (16 to 18%) than at lower CP levels (10 to 14%) by Awassi [9,29] and in Kıvırcık lambs [8] . Similarly Kaya et al [11] and Abbasi et al [30] reported higher growth for Morkaraman and Kooka lambs, respectively, at higher CP (16%) than at a lower level of dietary CP.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations